Substantiation of the process of deep tillage with agricultural machines of digging type - Bulgakov, Volodymyr; Mitkov, Vasyl; Мітков, Василь Борисович; Митков, Василий Борисович; Movchan, Vitalii; Мовчан, Віталій Федорович; Мовчан, Виталий Федорович; Mitin, Viacheslav; Мітін, В’ячеслав Миколайович; Митин, Вячеслав Николаевич; Ihnatiev, Yevhen; Ігнатьєв, Євген Ігорович; et al. (My University, 2020)
The paper considers the issue of deep tillage, the use of the latest technical advances, in order to develop new tillage implements that provide better tillage and reduce erosion. The main attention is paid to the preservation of soil fertility and the use of funds in organic farming. The aim of the work is to improve the process of mechanical tillage by digging by developing a new working body and the process of interaction of digging working bodies with the soil, which change its physical properties and improve environmental safety. The most promising for deep tillage is the digger in terms of both energy and agronomic indicators (reduction of compaction, preservation and restoration of water and air balance, preservation of humus, preservation of biomass). Rotary diggers with rotational movement of working bodies are more effective in comparison with diggers having oscillating movement of working bodies. As a result of studying the dependence of the angle of the blades, providing the movement of the formation on the surface of the working body, from their position on the trajectory, it was found that the smallest value (5…70) is the angle of inclination after turning the blade deepening. When lifting the formation from the bottom of the furrow to a certain height, the required angle of the blades increases, reaching a value of 28… 300 when overturning the formation at a height of 0.20…0.25 m.
Keywords: deep tillage; digger; energy consumption; degree of grinding; depth of cultivation